2009
DOI: 10.1101/gad.541309
|View full text |Cite
|
Sign up to set email alerts
|

Stu1 inversely regulates kinetochore capture and spindle stability

Abstract: The Saccharomyces cerevisiae CLASP (CLIP-associated protein) Stu1 is essential for the establishment and maintenance of the mitotic spindle. Furthermore, Stu1 localizes to kinetochores. Here we show that, in prometaphase, Stu1 assembles in an Ndc80-dependent manner exclusively at kinetochores that are not attached to microtubules. Stu1 relocates to microtubules when a captured kinetochore reaches a spindle pole. This relocation does not depend on kinetochore biorientation, but requires a functional DASH comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…Previous studies showed that the SS18-SSX-mediated nuclear accumulation of cyclin D1 in synovial sarcomas was mediated by the PI3K-Akt-GSK3β pathway [19,20] or aberrant β-catenin nuclear expression [21]. In general, cyclin D1 may also be activated without nuclear β-catenin overexpression via many different transcription signalings such as the MAPK pathway [22], JAK-STAT pathway [19,23], and Notch-CSL pathway [20]. In malignant mesothelioma, MAPK is frequently expressed and activated with phosphorylation of the extracellular-regulated kinase, the c-Jun amino-terminal kinase, and p38 [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the SS18-SSX-mediated nuclear accumulation of cyclin D1 in synovial sarcomas was mediated by the PI3K-Akt-GSK3β pathway [19,20] or aberrant β-catenin nuclear expression [21]. In general, cyclin D1 may also be activated without nuclear β-catenin overexpression via many different transcription signalings such as the MAPK pathway [22], JAK-STAT pathway [19,23], and Notch-CSL pathway [20]. In malignant mesothelioma, MAPK is frequently expressed and activated with phosphorylation of the extracellular-regulated kinase, the c-Jun amino-terminal kinase, and p38 [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Other outer kinetochore proteins: Additional proteins that localize to the outer kinetochore include the Stu1 and Stu2 proteins (orthologs of the vertebrate CLASP and XMAP215/ Dis1 proteins) Ortiz et al 2009;Kitamura et al 2010), the Slk19 protein (Zeng et al 1999), the Bik1 protein , and the four nuclear motor proteins, Kar3, Cin8, Kip1, and Kip3 (Tanaka et al 2005;Tytell and Sorger 2006;Pagliuca et al 2009). The localization of these proteins to kinetochores has been assayed by ChIP and/or microscopy, so it is difficult to determine how closely associated each protein is with the core kinetochore.…”
Section: Kmnmentioning
confidence: 99%
“…The CLASP (CLIP-associated protein) homolog is Stu1 (Akhmanova and Hoogenraad 2005;Ortiz et al 2009). CLASPs are plus-end-tracking proteins that stabilize MT plus ends by facilitating the incorporation of tubulin subunits (Maiato et al 2005).…”
Section: Microtubule-associated Proteinsmentioning
confidence: 99%
“…Stu1 is required for spindle formation (Yin et al 2002) and is found on the spindle. More recently, it has been shown that Stu1 binds unattached kinetochores in budding yeast (Ortiz et al 2009). Unattached kinetochores sequester Stu1 to prevent premature spindle stabilization, thereby keeping the two spindle poles together to facilitate sister kinetochore bi-orientation.…”
Section: Microtubule-associated Proteinsmentioning
confidence: 99%